Physics Simulation with Excel Spreadsheet - Laode Asmin (International Journal of Transdisciplinary Knowledge, 2021)
this study present several examples of using Excel spreadsheets to study and simulate physical phenomena, namely projectile motion, falling motion in The air, The wave function of particles in a one-dimensional box, and nuclear radioactive decay. Spreadsheets are used to analyze the motion of projectiles with and without resistance, falling objects with different terminal velocities, graphs of wave functions and probabilities with different values of n, i.e. n=1 to n=4, and nuclear decay with different probability values of P. The use of excel spreadsheets has proven to be very useful in the physics learning process, namely the rapid response to changes in data and graphs, according to the values given